Validasi Modul Pelatihan Disiplin Positif untuk Meningkatkan Praktik Pengasuhan pada Ibu Anak Prasekolah - Wijayanti Retnaningsih; Diana Setiyawati (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2019)
This study aimed to validate Positive Discipline Training Module to improve parenting practice. Module validation is conducted through two stages. The first is of content validation  which consisted of: 1) validation of contents on materials, methods, media, activities, worksheets, and time used in module, 2) validation of contents about legibility of module for family planning counselors) and two functional validation stages: 1) training of trainer (ToT) for family planning counselors and 2) training of Positive Discipline in mothers of preschool children. The result of the first stage content validity coefficient ranged between 0.750-0.958. The result of the second stage content validity ranged between 0.70-0.95. The result of ToT indicated that it could improve positive discipline knowledge on family planning counselors (Z = -2.032, p = 0.042). Mann Whitney U test showed that Positive Discipline Training could improve the practice of parenting in the experimental group (U = 0.000, p < 0.01). Thus, the module had sufficient content and functional validity. This research concluded that Positive Discipline Training Module is valid for improving parenting practice for mothers of the preschool children with family planning counselor trainers.